Comparing Descriptive Statistics for Retrospective Studies From One-per-Minute and One-per-Second Data - Salverda, Hylke H.; Dekker, Janneke; Witlox, Ruben S. G. M.; Dargaville, Peter A.; Pauws, Steffen; te Pas, Arjan B. (Frontiers in Pediatrics, 2022)
Background Large amounts of data are collected in neonatal intensive care units which could be used for research. It is unclear whether this data, usually sampled at a lower frequency, is sufficient for retrospective studies. We investigated what to expect when using one-per-minute data for descriptive statistics. Methods One-per-second inspiratory oxygen and saturation was processed to one-per-minute data and compared on average, standard deviation, target range time, hypoxia, days of supplemental oxygen, and missing signal. Results Outcomes calculated from data recordings (one-per-minute=92, one-per-second=92) showed very little to no difference. Sub analyses of recordings under 100 and 200 hours showed no difference. Conclusion In our study descriptive statistics of one-per-minute data were comparable to one-per-second and could be used for retrospective analyses. Comparable routinely collected once per minute data could be used to develop algorithms or find associations retrospectively.